The Influence of Investor Sentiments and Macroeconomic Factors on Bitcoin Price - Putra, Daffa Tegar Maulana; Pimada, Laila Masruro (Journal of Development Economic and Social Studies, 2026)
This study aims to analyse the influence of investor sentiment and macroeconomic factors on the price of Bitcoin in Indonesia. Investor sentiment is proxied by Google Trends and the Consumer Confidence Index (CCI), while macroeconomic factors include inflation and interest rates. The research utilizes monthly data from January 2021 to August 2024 and is analysed using the Autoregressive Distributed Lag (ARDL) method, with exchange rate, Brent oil price, and the Jakarta Composite Index (JCI) as control variables. The estimation results show that in the short term, Google Trends has a significant negative effect, while the CCI and interest rates have significant positive and negative effects, respectively. Conversely, in the long term, only the CCI has a significant negative effect on Bitcoin prices. These findings suggest that in the short term, Bitcoin price movements are more influenced by shifts in investor sentiment and monetary market conditions, whereas in the long term, rising consumer optimism may reduce interest in high-risk assets such as Bitcoin.